Managing term-time employment and study in Ireland - Merike Darmody; Emer Smyth (The Economic and Social Research Institute (ESRI), 2007)
An increasing amount of research now relates to full-time higher education students who work part-time during their study. However, little is known about this issue in the Irish context, despite the fact that the latter provides an interesting case-study due to its unprecedented economic growth in recent years and subsequent changes in the labour market. This paper attempts to address this gap in research and reports on a postal survey carried out among 3,900 higher education students. It aims to establish the profile of full-time higher education students engaged in part-time work during term-time. It also explores the motivation for engaging in paid work and possible implications of work-load on levels of life satisfaction. It is argued in this paper that inadequate policy attention to the changing profile of higher education students, their work-load and needs risks reinforcing inequalities among students.
Keywords: 330; higher education; part-time employment; survey; Ireland; logistic regression; Teilzeitarbeit; Arbeitszufriedenheit; Studierende; Soziale Lage; Schätzung; Irland